Out of Thin Air: Microbial Utilization of Atmospheric Gaseous Organics in the Surface Ocean - Arrieta, Jesús M.; Duarte, Carlos M.; Sala, M. Montserrat; Dachs, Jordi (Frontiers in Microbiology, 2016)
Volatile and semi-volatile gas-phase organic carbon (GOC) is a largely neglected component of the global carbon cycle, with poorly resolved pools and fluxes of natural and anthropogenic GOC in the biosphere. Substantial amounts of atmospheric GOC are exchanged with the surface ocean, and subsequent utilization of specific GOC compounds by surface ocean microbial communities has been demonstrated. Yet, the final fate of the bulk of the atmospheric GOC entering the surface ocean is unknown. Our data show experimental evidence of efficient use of atmospheric GOC by marine prokaryotes at different locations in the NE Subtropical Atlantic, the Arctic Ocean and the Mediterranean Sea. We estimate that between 2 to 27% of the prokaryotic carbon demand was supported by GOC with a major fraction of GOC inputs being consumed within the mixed layer. The role of the atmosphere as a key vector of organic carbon subsidising marine microbial metabolism is a novel link yet to be incorporated into the microbial ecology of the surface ocean as well as into the global carbon budget.